1999
DOI: 10.1023/a:1006909927287
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: 1. The authors compare oxidative injury to brain and kidney Na/K-ATPase using in vitro and in vivo approaches. The substrate dependence of dog kidney Na/K-ATPase was examined both before and after partial hydrogen peroxide modification. A computer simulation model was used for calculating kinetic parameters. 2. The substrate dependence curve for the unmodified endogenous enzyme displayed a typical curve with an intermediate plateau, adequately described by the sum of hyperbolic and sigmoidal components. 3. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…In the current study, the activity of Na + K + ATPase was found to be decreased in AD Tg mice, which is in line with other studies reporting decrease in the enzyme activity during aging [70, 71]. Na + K + ATPase is known to be highly susceptible to changes in the membrane lipids, which may be further attributed to the progressive increase in the lipid peroxidation [72, 73]. ROS overproduction inhibits the activity of ATPase via thiol- and lipid-dependent mechanisms [74].…”
Section: Discussionsupporting
confidence: 90%
“…In the current study, the activity of Na + K + ATPase was found to be decreased in AD Tg mice, which is in line with other studies reporting decrease in the enzyme activity during aging [70, 71]. Na + K + ATPase is known to be highly susceptible to changes in the membrane lipids, which may be further attributed to the progressive increase in the lipid peroxidation [72, 73]. ROS overproduction inhibits the activity of ATPase via thiol- and lipid-dependent mechanisms [74].…”
Section: Discussionsupporting
confidence: 90%
“…One of the possible mechanisms of neuroprotective effect of punicalagin was an improvement of Na+/K+ ATPase activity, an integral membrane protein which maintains electrolyte and fluid balance in cells, organs, and the whole body [54]. ATPase is known to be highly susceptible to changes in the membrane lipids, which may be further attributed to the progressive increase in the Lipid peroxidation (LPO) products especially MDA levels [55, 56]. Modification in Na + K + −ATPase activity may induce neuronal death with features of both apoptosis and necrosis [57].…”
Section: Discussionmentioning
confidence: 99%
“…[5253] Na + K + -ATPase is known to be highly susceptible to changes in the membrane lipids, which may be further attributed to the progressive increase in the LPO. [5455] ROS overproduction inhibits the activity of ATPase via thiol- and lipid-dependent mechanisms. [56] It has been demonstrated that the reduced activity of Na + K + -ATPase caused by oxidative stress cannot drive the ion pumps to maintain depolarization of neurons and, thus, may become lethal to neurons.…”
Section: Discussionmentioning
confidence: 99%